2016
DOI: 10.3847/0004-637x/820/1/60
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-Island Contraction and Particle Acceleration in Simulated Eruptive Solar Flares

Abstract: The mechanism that accelerates particles to the energies required to produce the observed high-energy impulsive emission in solar flares is not well understood. Drake et al. proposed a mechanism for accelerating electrons in contracting magnetic islands formed by kinetic reconnection in multi-layered current sheets (CSs). We apply these ideas to sunward-moving flux ropes (2.5D magnetic islands) formed during fast reconnection in a simulated eruptive flare. A simple analytic model is used to calculate the energ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 104 publications
(147 reference statements)
5
75
0
Order By: Relevance
“…ARMS has been used to study numerous dynamic phenomena in the solar atmosphere, including coronal jets (Pariat et al 2015;Wyper et al 2016;Karpen et al 2017), theinteraction between closed and open fields at streamer boundaries (Edmondson et al 2009(Edmondson et al , 2010aMasson et al 2013;Higginson et al 2017a,b), and the examination of plasmoid-unstable reconnection and magnetic island evolution (Paper I; Guidoni et al 2016;Lynch et al 2016). …”
Section: Numerical Simulationsmentioning
confidence: 99%
“…ARMS has been used to study numerous dynamic phenomena in the solar atmosphere, including coronal jets (Pariat et al 2015;Wyper et al 2016;Karpen et al 2017), theinteraction between closed and open fields at streamer boundaries (Edmondson et al 2009(Edmondson et al , 2010aMasson et al 2013;Higginson et al 2017a,b), and the examination of plasmoid-unstable reconnection and magnetic island evolution (Paper I; Guidoni et al 2016;Lynch et al 2016). …”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Early magnetotail studies suggested that magnetic reconnection can happen in an episodic fashion (Coppi et al 1966;Schindler 1974), with subsequent observations supporting this view (Hones et al 1976). In coronal conditions, recent numerical models have shown that magnetic reconnection can occur in a repetitive regime (e.g., Kliem et al 2000;Drake et al 2006;Linton & Longcope 2006;Guidoni et al 2016). Repeated episodes of magnetic reconnection itself could account for the modulation of emission in many different wavelengths.…”
Section: Introductionmentioning
confidence: 89%
“…The large modulation depths of the non-thermal emission during this time suggest that the pulsations are a result of episodic reconnection. The timescale would then be determined by either dynamic or periodic variations of the magnetic reconnection process such as multi-island reconnection in coronal current sheets (Drake et al 2006;Guidoni et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…To resolve these tearing instabilities and their resulting magnetic islands in numerical simulations, a high resolution at the current sheets is necessary. Recent progress in this area has been made by Karpen et al (2012), Guidoni et al (2016) and Hosteaux et al (2018). They are not present at the front of an inverse CME, but at the rear because this is where a current sheet forms when the CME has the same polarity as the solar wind.…”
Section: Synthetic Satellite At L1mentioning
confidence: 99%